Green Innovation: Driving Sustainable Performance in Yogyakarta’s Hospitality Industry - Adi Syahputra, Alfa; Irhas Effendi, Mohammad; Kristanto HC, R. Heru (International Journal of Economics, Business and Innovation Research, 2024)
This research employs a quantitative approach with a descriptive design to analyze relationships among variables in the hospitality industry of Yogyakarta. The study investigates three independent variables—Environmental Regulations, Management Commitment, and Resource Capabilities—alongside one dependent variable, Sustainable Performance, and one mediating variable, Green Innovation. Utilizing non-probability and purposive sampling methods, data were gathered from hospitality businesses in Yogyakarta. Analysis techniques included descriptive statistics, outer model evaluation for validity and reliability, and inner model assessment through Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). Findings reveal significant positive impacts of environmental regulations, management commitment, and resource capabilities on green innovation, which subsequently enhances sustainable performance. The results suggest that stringent regulations and strong management support effectively drive green innovation, leading to improved sustainability outcomes. The study recommends that local governments strengthen environmental regulations and that hospitality firms implement training programs to foster further green initiatives.